2020
DOI: 10.1093/annweh/wxaa119
|View full text |Cite
|
Sign up to set email alerts
|

Labour Market Attachment, Workplace Infection Control Procedures and Mental Health: A Cross-Sectional Survey of Canadian Non-healthcare Workers during the COVID-19 Pandemic

Abstract: Background The COVID-19 pandemic has led to large proportions of the labour market moving to remote work, while others have become unemployed. Those still at their physical workplace likely face increased risk of infection, compared to other workers. The objective of this paper is to understand the relationship between working arrangements, infection control programs (ICP), and symptoms of anxiety and depression among Canadian workers, not specifically working in healthcare. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 23 publications
5
71
0
2
Order By: Relevance
“…Previous studies have also reported an increase in anxiety and depression in interpersonal work. 19 Additionally, in places like offices, workers share a relatively small space. Thus, the fact that individuals have limited control over maintaining the recommended three Cs strategy for infection prevention at work can be a major cause of stress.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have also reported an increase in anxiety and depression in interpersonal work. 19 Additionally, in places like offices, workers share a relatively small space. Thus, the fact that individuals have limited control over maintaining the recommended three Cs strategy for infection prevention at work can be a major cause of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing infection control policies and implementing infection control measures in the workplace can be beneficial for the mental health of workers, and a sense of trust and security that infection control measures in the workplace are adequate will alleviate anxiety. 15,18,19 Use of personal protective equipment when conducting interpersonal tasks and access to testing in case of suspected infectious contact can also ease anxiety. 18,19 Additionally, public awareness, such as through access to correct information and avoiding excessive exposure to the media, may be useful for reducing anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations